The Politics and Ethics of Representation in Qualitative Research Addressing Moments of Discomfort (Taylor & Francis, 2022)
This book offers insights on politics and ethics of representation that are relevant to researchers concerned with struggles for justice. It takes moments of discomfort in the qualitative research process as important sites of knowledge for exploring representationalpractices in critical research. The Politics and Ethics of Representation in Qualitative Research draws on experiences from research processes in nine PhD projects. In some chapters, ethical and political dilemmas related to representational practices are analyzed as experienced in fieldwork. In others, the focus is on the production of representation at the stage of writing. The book deals with questions such as: What does it mean to write about the lives of others? How are ethics and politics of representation intertwined, and how are they distinct? How are politics of representation linked to a practice of solidarity in research? What are the im/possibilities of hope and care in research? Drawing on grounded empirical research, the book offers input to students, PhDs, researchers, practitioners, activists and others dealing with methodological dilemmas from a critical perspective. Instead of ignoring discomforts, or describing them as solved, we stay with them, showing how such a reflective process provides new, ongoing insights. The Open Access version of this book, available at http://www.taylorfrancis.com/books/e/9780429299674, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.